Earnings manipulation and cash holdings: a Beneish M-score analysis in G7 nations - Serdar Ozkan; Loulwah Alfarhan (Cogent Business & Management)
This study examines the relationship between earnings manipulation and cash holdings in non-financial firms across G7 countries from 2006 to 2022, using 111,640 firm-year observations from 9,766 listed companies. Earnings manipulators are identified using the Beneish M-Score. The analysis explores how manipulation relates to cash-holding practices across institutional settings. While prior studies mainly focused on single-country contexts, this study applies a unified detection approach in a cross-country setting, offering broader insights into how governance and culture influence corporate liquidity policies. Results show that manipulators hold significantly more cash than non-manipulators in the US, UK, Canada, France, and Italy, but not in Germany and Japan. This variation reflects firm-level factors such as overvaluation and financial distress, and country-level traits like ownership concentration, strength of accounting and auditing enforcement, and individualism. In France and Italy, precautionary cash accumulation is linked to moderate enforcement and concentrated ownership. In contrast, the US, UK, and Canada exhibit strong enforcement and individualistic cultures, encouraging cash hoarding to manage litigation and governance pressures. Overall, the results underscore the interplay between firm incentives and institutional environments in shaping fraudulent firms’ liquidity strategies.